Perancangan User Experience Aplikasi Toko Air Minum menggunakan Metode Pendekatan Human Centered Design (Studi Kasus: Toko Berkat di Cibubur) - Reynard Euginio Tjokro; Agi Putra Kharisma; Riswan Septriayadi Sianturi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Water Drinking Store application designed to help store owners in providing good service and help customers make transactions easier. This research conducted to design a good user experience for its users. In making this design using the HCD (Human-Centered Design) method that has 3 main stages, namely inspiration, ideation, and implementation. Application testing is carried out using usability testing and filling out User Experience Questionnaire (UEQ) for 2 types of users. The test results for the owner's application show an effectiveness value of 92.5%, an efficiency value of 0.12 goals/second, and a user satisfaction value of 82.5. Meanwhile, the customer application shows an effectiveness value of 90.18%, an efficiency value of 0.216 goals/second, and a user satisfaction value of 81.43. Then the UEQ results on owner's application, showed excellent value in the attractiveness, efficiency, dependability, stimulation, and novelty aspects and had good value in the perspicuity aspect. Meanwhile, the customer application had good value in the attractiveness, efficiency, and dependability values and had above average value in the perspicuity, stimulation, and novelty aspect. These results shows that the design solution is acceptable with good usability values ​​and has user experience values ​​that each aspect is above average.